Recent trends in acetone, butanol, and ethanol (ABE) production - Keikhosro Karim (Biofuel Research Journal, 2015)
Among the renewable fuels considered as a suitable substitute to petroleum-based gasoline, butanol has attracted a great deal of attention due to its unique properties. Acetone, butanol, and ethanol (ABE) can be produced biologically from different substrates, including sugars, starch, lignocelluloses, and algae. This process was among the very first biofuel production processes which was commercialized during the First World War. The present review paper discusses the different aspects of the ABE process and the recent progresses made. Moreover, the microorganisms and the biochemistry of the ABE fermentation as well as the feedstocks used are reviewed. Finally, the challenges faced such as low products concentration and products` inhibitory effects on the fermentation are explained and different possible solutions are presented and reviewed.